14-3-3 proteins are part of an abscisic acid-VIVIPAROUS1 (VP1) response complex in the Em promoter and interact with VP1 and EmBP1. - Schultz, T F (1998)
Protein-DNA complexes were formed when nuclear extracts from embryogenic rice suspension cultures or maize embryos were incubated with an abscisic acid-VIVIPAROUS1 (VP1) response element (Em1a) from the Em promoter. Monoclonal antibodies generated to GF14, a 14-3-3 protein from plants, resulted in gel retardation of the Em1a-protein complexes. Antibodies generated to the C and N termini of GF14 detected protein isoforms in rice nuclear and cytoplasmic extracts, but no differences in distribution of the GF14 isoforms were recognized between the nucleus and cytoplasm or when abscisic acid-treated and untreated tissues were compared. When recombinant GF14 fusion proteins from rice were added to nuclear extracts, novel complexes were formed that required the dimerization domain of GF14. Chemical cross-linking showed that GF-14 interacted with the basic leucine zipper factor EmBP1, which binds specifically to Em1a, and with VP1, which transactivates Em through Em1a. GF14 proteins from rice were shown to interact with VP1 in yeast through the dimerization domain of GF14. Our results indicated that GF14 interacts with both site-specific DNA binding proteins (i.e., EmBP1) and tissue-specific regulatory factors (i.e., VP1) and may provide a structural link between VP1 and the Em1a transcriptional complex.